'Blood is thicker than water' : non-royal consanguineous marriage in ancient Egypt : an exploration of economic and biological outcomes - Robinson, Joanne-Marie, (Archaeopress Egyptology ;, 2020)
This volume presents evidence for non-royal consanguineous marriage in ancient Egypt. The evidence was collated from select sources from the Middle Kingdom to the Roman Period, and it has been used to investigate the potential economic and biological outcomes, particularly beyond the level of sibling and half-sibling unions.